Pengaruh Fasilitas dan Motivasi Karyawan PT.Indo Citra Pacific - Rizka Meidina Utama; Akhmad Fauzi (Jurnal Ilmiah Wahana Pendidikan, 2023)
A company needs to pay attention to control and encourage good performance of its employees because it will become one of the main driving factors for the continuity of operations in the company. When employees are given the right tools, good working conditions, and good working motivation, it can create a more conducive working atmosphere and make work more effective. The purpose of this study was to evaluate the positive influence, significance of the facilities, and work motivation of employees at PT. Indocitra Pacific. This research is using saturated sampling method and questionnaire data collection using a five-point Likert scale as a measurement. The population and sample used in this study involving 32 respondents which are all permanent employees of PT. Indocitra Pacific and is using Partial Least Square (PLS) as analysis method. Based on the results of the research, it was found that a good work facility and a good motivation of working has a positive and significant effect on the performance of employees of PT. Indocitra Pacific.